Aerospace materials and applications - Bhat, B. N. (American Institute of Aeronautics and Astronautics, Inc., 2018)
"The present volume is focused on documenting the novel processing, fabrication, characterization, and testing approaches that are unique to aerospace materials/structures/systems"--Preface
Keywords: Aeronautics -- Materials.; Astronautics -- Materials.; Aerospace engineering.; elektronické knihy; electronic books